Power Heritage: Gamified RPG Maker MV Based on Numeracy Literacy with Elaboration of Pacitan’s Local Wisdom for Elementary Schools - Putri, Marsanda Avilia; Surayanah (Journal of Development Research, 2025)
The purpose of this study is to develop RPG Maker MV gamification learning media based on numeracy literacy with elaboration of Pacitan local wisdom on energy crisis material for sixth grade elementary school students. The research method used is development research with the ASSURE model, which consists of six stages. The research subjects were sixth-grade students at SD Negeri 2 Ketepung and SD Negeri Arjowinangun as the initial observation targets, as well as SD Negeri 2 Ketepung, SD Negeri Pacitan, and SD Negeri 1 Wonogondo as the research targets. The data, in the form of needs analysis results, media validation, practicality tests, and trial test results, were analyzed quantitatively according to the scale used, as well as qualitatively to describe the research results. The results of this study were a gamified learning medium entitled Power Heritage with IPAS material content on “Energy Crisis” which was considered highly valid by subject matter experts, media experts, instrument experts, and teaching module experts, as well as highly practical according to teachers and students. This media has been proven to have a significant impact on students' analytical thinking skills, with the average test score increasing from 56.21% on the pre-test to 82.8% on the post-test. The integration of numeracy literacy in the application is realized in every storyline of the game. Meanwhile, learning based on local wisdom has a significant influence on students' interest in operating the application.